Bristol from below : law, authority and protest in a Georgian city - Poole, Steve, 1957-; Rogers, Nicholas (Studies in early modern cultural, political and social history, 2017)
Captures the substance and scale of popular politics and protest in Bristol over the course of the long eighteenth century.